PENGARUH MOTIVASI TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (Survei pada Mahasiswa Akuntansi Fakultas Ekonomi Universitas Slamet Riyadi Surakarta) - Musliamawan Setya Aji; Rispantyo Rispantyo; Djoko Kristianto (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
Professional accounting education is supplementary education in tertiary education after a bachelor of economics program in an accounting study program. The aim of this research is to analyze the significance of the influence of quality, career and economic motivation on the interest of accounting students to attend accounting education. This research was conducted at the University of Slamet Riyadi Surakarta. The type of data used is qualitative data and quantitative data. Source of data comes from primary data and secondary data. Data analysis techniques used multiple linear regression analysis. The results of this study indicate the influence of quality motivation (X1) on the interest of accounting students to follow the accounting profession education. The influence of career motivation (X2) on the interest of accounting students to attend accounting professional education. The influence of economic motivation (X3) on the interest of accounting students to attend accounting professional education.